A Review on Transitional Implications for Retiring Elite Athletes: What Happens When the Spotlight Dims? - McManus, Alexandra; Smith, Jennifer (Bentham Open, 2008)
The purpose of this investigation was to examine the factors affecting an elite athlete’s transition from the sports environment, and identify opportunities for interventions to facilitate a positive transition into post-sports life. Articles were identified through a systematic keyword and database search and were examined using the components of Schlossberg’s Model of Human Adaptation to Transition (characteristics of the transition, the individual and the pre and post environment). The greatest contributors to a difficult transition include involuntary retirement (injury or deselection), a strong, exclusive athletic identity, and lack of pre-retirement planning and support services. However, gaps exist in the scope of programs to address broader adaptation issues. Greater emphasis should be directed towards the psychological, social and physical transitions experienced by elite athletes prior to and after retirement to ensure a positive adaptation into post-sports life.